EXPLORING COPING STRATEGIES FOR STRESS MANAGEMENT AMONG UNDERGRADUATE MEDICAL STUDENTS - Tariq, Ayesha; Nabia Tariq; Kiran Jabeen; Sajida Naseem (Journal of Ayub Medical College Abbottabad, 2022)
Background: College is the time where most mental health disorders are triggered. Due to an extremely strenuous curriculum, medical students are prone to develop high levels of stress. Teaching students stress management skills can be crucial for their mental and physical well being. Objectives of the study were to measure perceived stress level among undergraduate medical students of Year 5 using PSS Scale, and to explore if students find stress management activities helpful in reducing stress. Methods: It was a quasi experimental study.5th year medical students were asked to take part in a full day workshop regarding stress management. During the day they were introduced to different stress management activities. Stress levels were measured using PSS before the workshop and 1 month after the workshop. Results: On the PSS 1, 17.9% participants scored in the low stress category, 61.1% participants scored in the moderate stress category and 21.1% scored in the high stress category. On the PSS 2, 11.6% participants scored in the low Stress category, 76.8% participants scored in the moderate stress category and 11.6% scored in the high stress category. Pre and post intervention PSS stress results were statistically significant, p< 0.05. Conclusion: Majority of the final year students had moderate stress. Training undergraduate medical students in integrated stress relieving activities can help lower their perceived stress.